THE EFFECT OF GREEN MARKETING, BRAND IMAGE, AND E-WOM ON PURCHASING DECISIONS FOR THE BODY SHOP INDONESIA PRODUCTS - Agustin, Nengliya; Azzahra, Fairuzzia; Hernidatiatin, Lis Tatin (Universitas Nusa Cendana, 2025)
This study aims to determine the effect of green marketing, brand image, and e-WOM on purchasing decisions for The Body Shop Indonesia products. The sampling method was purposive; the questionnaire was distributed to 109 respondents. Data analysis using Smart Partial Least square (SmartPLS), by testing the outer model, and inner model. The results showed that green marketing variables had a positive but insignificant effect on purchasing decision variables, while brand image and e-WOM variables had a positive and significant effect on purchasing decision variables. The e-wom variable has the greatest effect on the purchasing decision variable. Keywords: Green Marketing; Brand Image; e-WOM; Purchasing Decision